Innate-like lymphocytes 1 - Hayday, Adrian (Henry Stewart Talks, 2009)
Innate like lymphocytes, Structural representation of antigen receptors, Introduction to "unconventional" lymphocytes, Innate-like T cells and tissue immune surveillance, Information flow: from challenge to DC to T cell, Immune response by conventional lymphocytes, Conventional immunity strength and weaknesses, Tissue associated T cells, IEL, one of the largest T cell subsets, Gamma-delta T cells, receptor and gene segment, Phenotypes of "innate-like" T cells, Intestinal intraepithelial lymphocytes, Stress induced MHC class 1B, Rae-1 induction rapidly promotes infiltration, A role for gamma-delta T cells in carcinogenesis, Early tumor surveillance, Spontaneous pathology in TCRgamma-/- mouse, Phenotypic rescue with precursors of DETC, Application human disease, Key cells that bear the NKG2D receptor, Direct activation of tissue-associated lymphocytes, Functional differentiation of Innate-like T cells, "Slow" activation of adaptive lymphoid cells, "Fast" activation of innate-like lymphocytes?, Discrete (CD27+/-) gamma-delta cell subsets, Cytokines production in CD27-/- mice, Gamma-delta cell development in the thymus, Acquiring functional competence working model, Gamma-delta cells and virus/bacterial infection, Immunity in the very young